Antithrombotic Treatment for Acute Extracranial Carotid Artery Dissections: A Meta-Analysis. Issue 2 (August 2015) - Chowdhury, M.M.; Sabbagh, C.N.; Jackson, D.; Coughlin, P.A.; Ghosh, J.
Abstract : Introduction: Carotid artery dissection is a leading cause of stroke in younger patients, with an associated prevalence of 2.6–3.0 per 100, 000 population. This meta-analysis aims to determine whether in patients managed medically, treatment with anticoagulants or antiplatelet agents was associated with a better outcome with respect to mortality, ischaemic stroke, and major bleeding episodes. Patients and methods: A comprehensive search strategy was employed of the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE (January 1966 to March 2015), and EMBASE (January 1980 to March 2015) databases. Primary outcomes were death (all causes) or disability. Secondary outcomes were ischaemic stroke, symptomatic intracranial haemorrhage, and major extracranial haemorrhage during the reported follow-up period. Results: No completed randomized trials were found. Comparing antiplatelets with anticoagulants across 38 studies (1, 398 patients), there were no significant differences in the odds of death (effects size, ES, −0.007, p = .871), nor in the death and disability comparison or across any secondary outcomes. Conclusion: There were no randomised trials comparing either anticoagulants or antiplatelets with control, thus there is no level 1 evidence to support their routine use for the treatment of carotid artery dissection. Also, there were no randomised trials that directly compared anticoagulants with antiplatelet drugs, and the reported non-randomised studies did not show any evidence of a significant difference between the two.